Divine Lola : a true story of scandal and celebrity - Morató, Cristina, 1961- (Amazon Crossing, 2021)
The extraordinary story of one of the most famous women of the 19th century, a woman marked by the scandal that had the world at their feet. Lola Montes was not her real name, nor was she Spanish, but she dazzled a whole era with her breathtaking beauty and passionate temperament. Dancer, adventurerer and courtesan, her life was a succession of travel, scandals, and eccentricities. Posing as a Andalusian dancer, she debuted at the most important theaters of the world, although her artistic talent left much to be desired. But nothing prevented the Irish Elisabeth Gilbert, her real name, from succeeding in everything she did. She trained with the most famous writers, politicians, musicians and aristocrats of her time, such as Alexandre Dumas, Honoré de Balzac and George Sand. She was married three times and had a long list of lovers, including the composer Franz Liszt, who lived with a passionate romance. And, above all, she fell to King Ludwig I of Bavaria, who named her the countess of Landsfeld. Due to her love, the monarch was forced to abdicate in 1848. After her adventures in Europe, the dancer was shipped to the United States, where she lived the gold fever and acted for the rude miners. Divine Lola takes us to exotic and remote, from her native Ireland to the magic of India; to cities such as Paris, London, Munich, where she dazzled with her Spanish dances, and to the dangerous lands of California and Australia where she lived as a fearless pioneer.